Zauj and Imara'ah in The Qur'an, Says Mutaradif (A Pre-Emptive Study of the Quran's Semantic Interpretation by Toshihiko Izutsu) - Aini, Sabilla Qurratu; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The terms lafadz, which means "zauj," and "imra'ah," which means "wife," are two examples from the Qur'an that illustrate the metaphorical meaning of women. The term "mutaradif" in the Qur'an refers to a phrase that, although having the same meaning, is not quite the same because each of the Qur'anic lafadz-which have individual meanings-contains parts of balaghah. The study of the terms zauj and imra'ah, as well as synonymity (Mutaradif) in the Qur'an, will be covered in this paper. With the help of these word pairings, it is anticipated that this study would be able to identify instances of synonymy in the Qur'an as well as their absence. What do the terms "imra'ah" and "zauj" imply in the Qur'an? How is the semantic field used to view the link between the words "zauj" and "imra'ah"? What does the Qur'anic term "zauj" and "imra'ah" mean in context? Researchers employ the Qur'anic lexicon and important concepts through semantic analysis, a method first introduced by Toshihiko Izutsu in an effort to address the Qur'anic worldview (weltanschauung). There are six connotations associated with the term Zauj: spouse, companion, animal, plant, and group. And prior to Islam, it meant a mattress that offered weather protection. There are two ways to write the word Imra'ah: إمرأة and إمرأت. إمرأة is the term used to refer to women in general. In surahs al-Nisa:12, al-Ahzab:50, al-Naml:23, and AN-Nisa:128 are a few examples.